Impact of the introduction of falls risk assessment toolkit on falls prevention and psychotropic medicines’ utilisation in Walsall: an interrupted time series analysis - Mohammed Ibrahim Aladul; Stephen Robert Chapman; Bharat Patel (BMJ Open)
Objective To determine the impact of the introduction of a falls risk assessment toolkit (FRAT) in a UK medical centre on the number and cost of non-elective admissions for falls and psychotropic medication utilisation.Design Interrupted time series analysis quantifying the number and cost of non-elective admissions for falls and primary care use data for Rushall Medical Centre before and after the implementation of FRAT at July 2017.Setting Data on the monthly number and cost of non-elective admissions for falls and number of referrals and assessment to the falls service were provided by Walsall Clinical Commissioning Group. Primary care prescribing cost and volume data for Rushall Medical Centre was derived from the Openprescribing.net website for prescriptions dispensed between April 2015 and November 2018.Primary and secondary outcome measures The number and cost of non-elective admissions for falls and number of referrals and assessment to the falls service, and the volume of utilisation of psychotropic medicines.Results Following the implementation of FRAT at Rushall Medical Centre in July 2017, the number of non-elective admissions for falls decreased at a rate of 0.414 admissions per month (p<0.033, 95% CI –0.796 to –0.032). The utilisation of psychotropic medications (alimemazine, citalopram, escitalopram, fluoxetine, mirtazapine, olanzapine and risperidone) decreased. The expenditure on psychotropic medications prescribed/used at Rushall Medical Centre decreased by at least £986 per month (p<0.001, 95% CI –2067 to –986).Conclusions The implementation of FRAT at Rushall Medical Centre was associated with a reduction in the number of non-elective admissions for falls. Assessment of these patients together with deprescribing of psychotropic medications resulted in a reduction in the number of non-elective admissions for falls and associated costs.